2010
DOI: 10.4414/smw.2010.13119
|View full text |Cite
|
Sign up to set email alerts
|

APOE epsilon status in Hungarian patients with primary progressive multiple sclerosis

Abstract: Our findings suggest that the presence of the ε2 and ε4 alleles may play a role in the development of the disease. However, if any type of the disease has already developed the alleles show no association with the clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
7
0
2
Order By: Relevance
“…Our results are line with previous observations that unique underlying pathobiologic factors may contribute to the development of PP vs. relapsing forms of MS and a propensity for spinal cord involvement [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. In support of the notion that PP represents a unique form of the disease, which may be thought of a different from the RR spectrum, Bramow and colleagues [ 23 ] showed that PPMS is characterized histologically as having a robust regulatory and reparative mechanism protecting the brain's white matter, while the spinal cord tends to be vulnerable to impaired repair and recurrent demyelination; this was in distinction to findings from patients on the relapsing disease spectrum.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are line with previous observations that unique underlying pathobiologic factors may contribute to the development of PP vs. relapsing forms of MS and a propensity for spinal cord involvement [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. In support of the notion that PP represents a unique form of the disease, which may be thought of a different from the RR spectrum, Bramow and colleagues [ 23 ] showed that PPMS is characterized histologically as having a robust regulatory and reparative mechanism protecting the brain's white matter, while the spinal cord tends to be vulnerable to impaired repair and recurrent demyelination; this was in distinction to findings from patients on the relapsing disease spectrum.…”
Section: Discussionsupporting
confidence: 92%
“…The APOE E4 allele was also found to be overrepresented in PPMS patients (53.3%) relative to healthy controls (8.9%, p < 0.0001) or RRMS patients (24.4%, p ¼ 0.009) in a Hungarian case-control study of 45 PPMS, 45 RRMS, and 45 healthy controls (Losonczi et al, 2010). Conversely, the 2 allele was underrepresented in PPMS patients (8.9%) relative to healthy controls (37.8%, p ¼ 0.002) or RRMS patients (48.9%, p < 0.0001).…”
Section: Apoementioning
confidence: 90%
“…Одним из факторов, лежащих в основе фенотипических различий между ППРС и РРС, может быть генетическая гетерогенность этих форм РС. Действительно, несмотря на существование универсальных генетических маркеров, носительство которых судя по всему ассоциировано с РС независимо от его формы [7,8], в ряде работ [9,10] выявлены также однонуклеотидные полиморфизмы (single nucleotide polimorptisms -SNP), ассоциация аллелей и генотипов которых наблюдается только в случае ППРС и не характерна для РРС. К сожалению, вследствие значительных различий в распространенности двух форм РС большинство генетических исследований выполнено для больных РРС.…”
Section: Introductionunclassified
“…Исследования не-HLA-генов позволили выявить в некоторых популяциях участие в развитии ППРС полиморфных вариантов ряда генов, продукты которых вовлечены в процесс воспаления (CTLA4, IL4, IL4R, IL7RA, TNF, APOE и др.) [9,10,12,13], а также генов, участвующих в нейродегенеративных процессах: CRYAB, CB1, GSK3b и др. [12,14,15].…”
Section: Introductionunclassified